Instrumentos de identificação precoce dos sinais de risco para o transtorno do espectro autista: Revisão integrativa da literatura - Leticia Silva Carvalho Dias; Catarina Marcos Moldão; Maria Eva Araújo Carvalho Bertoldo; Thayane Rodrigues de Santana; Yandra Giovanna de Oliveira Cunha; Ingrid Ribeiro Soares da Mata; Marilucia Rocha de Almeida Picanço (Sociedade Brasileira de Pediatria, 2022)
INTRODUCTION: Screening children for risk factors associated with autism spectrum disorders is essential to mitigate the potential impact of communication and behavioral impairment. OBJECTIVES: This study aims to identify and analyze the screening tools used with children aged 12-24 months available in Brazilian and international indexed literature. METHODS: This literature review included articles published from 2010 to 2020 in the following platforms: Google Scholar, Medline, PubMed, CAPES, Lilacs and SciELO. RESULTS: We selected 15 articles describing 15 screening tools, three of which had been translated into Portuguese (MCHAT, PREAUT and IRDI). CONCLUSIONS: Given the relevance of early interventions for children with autism spectrum disorders, more studies about screening tools are needed at a national level. At an international level, methods with higher sensitivity and specificity used in the analysis of autism spectrum disorders need to be standardized.